2014
DOI: 10.1016/j.ijgo.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of expectant management of stable mild to moderate chronic hypertension as compared with planned delivery

Abstract: Mild to moderate chronic hypertension could be managed expectantly up to 41 weeks if SPE did not develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
(57 reference statements)
1
15
0
1
Order By: Relevance
“…There were two perinatal deaths in the included trials, both from GRIT, one in each group. Inclusion of aggregate data from Hamed et al . on placental abruption, intrauterine growth restriction, NICU admission, and perinatal mortality did not change these results significantly (Table ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…There were two perinatal deaths in the included trials, both from GRIT, one in each group. Inclusion of aggregate data from Hamed et al . on placental abruption, intrauterine growth restriction, NICU admission, and perinatal mortality did not change these results significantly (Table ).…”
Section: Resultsmentioning
confidence: 94%
“…References (Refs): HYPITAT‐I, Koopmans (2009); DIGITAT, Boers (2010); Hamed (2014); Deliver or Deliberate, Owens (2014); HYPITAT‐II, Broekhuijsen (2015); GRIT, GRIT Study Group (2003).…”
Section: Resultsmentioning
confidence: 99%
“…In relation to hypertensive disorders broadly, Cluver et al [118] conducted a Cochrane review comparing planned early birth versus EM from 34 weeks to term. The review identified five RCTs, with a total of 1819 women [134][135][136][137][138]. Both the HYPITAT-I (Hypertension and Preeclampsia Intervention Trial at Term) and HYPITAT-II trials were included [134,135].…”
Section: Hypertension/preeclampsiamentioning
confidence: 99%
“…The HYPITAT-II trial compared IOL at 34-36+6 weeks to EM until 37 weeks for pregnant women with gestational hypertension, mild preeclampsia, or deteriorating chronic hypertension [134]. Three further RCTs compared planned early birth via IOL or CS versus EM for pregnant women with mild preeclampsia or gestational hypertension [136,138] or moderate essential chronic hypertension [137]. The review found a lower risk of composite maternal mortality and severe morbidity for women randomised to receive planned early birth.…”
Section: Hypertension/preeclampsiamentioning
confidence: 99%
“…Searching ClinicalTrials.gov and PubMed using the search terms “chronic hypertension,” “pregnancy,” and “induction of labor,” we identified a single randomized control trial investigating the gestational age of delivery in women with chronic hypertension (11) where 74 women were randomized to elective delivery at 37 weeks versus expectant management until 41 weeks. No difference was found in the risk of severe preeclampsia between groups; however, as the average gestational age at delivery in the planned delivery was 35 weeks, the lack of difference may be due to management choices and the risk of preeclampsia between recruitment and delivery, rather than lack of benefit to delivery at 37 weeks.…”
Section: Discussionmentioning
confidence: 99%